Scheme and study of a model predictive controller for statcom to solve the stability issues of a single machine infinite bus - Anajjar, Abdelrahman (2014)
This paper preface the model of linearized Single-machine infinite-bus power systems with (STATCOM) stating the usage of the model in inspecting the damping effect of the STATCOM and planning a STATCOM controller toward improving the stability of power system alternation. The power arrangements are deliberated in single-machine infinite-bus. To elucidate the speculative setting up of Model Predictive Control (MPC) and its practice in power system an attempt has been arranged to increase MPC controller intended at Single machine Infinite bus system (SMIB) together with FACTS devices. Explaining the effect of the constraints and tuning the weight. The recommended process is held with MATLAB simulation outcomes.